Implementation of Educational Supervision to Improve the Quality of Education in Madrasah - Utami, Batina Yulia; Elmanisar, Velnika; Ose, Fitria; Marsidin, Sufyarman; Rifma, Rifma (Postgraduate School, Universitas Negeri Padang, 2024)
The decline in the quality of education is caused by various factors, including unprofessional educational supervision, limitations in learning activities, and the practice of corruption, collusion, and nepotism. Ineffective supervision results in a gap between supervisors and teachers, so that the quality of learning is not optimal. In addition, the practice of cheating in national exams which is still rampant is also a serious concern. To overcome this problem, hard work is needed from educational thinkers and practitioners to improve the quality of education through professional supervision and breaking the chain of corruption. This study aims to identify problems in the education system in Indonesia and emphasize the importance of supervision in improving the quality of education. The research method used is a literature study, with analysis of various secondary data sources such as books and journals. The results of the study indicate that effective supervision can improve the quality of the learning process and learning environment, so there needs to be a focus on improving teacher skills through professional guidance.